Aspirin influences megakaryocytic gene expression leading to up‐regulation of multidrug resistance protein‐4 in human platelets. (December 2014) - Massimi, Isabella; Guerriero, Raffaella; Lotti, Lavinia Vittoria; Lulli, Valentina; Borgognone, Alessandra; Romani, Federico; Barillà, Francesco; Gaudio, Carlo; Gabbianelli, Marco; Frati, Luigi; Pulcinelli, Fabio M.
<x xml:space="preserve">Abstract</x> Aim The aim of the study was to investigate whether human megakaryocytic cells have an adaptive response to aspirin treatment, leading to an enhancement of multidrug resistance protein‐4 (MRP4) expression in circulating platelets responsible for a reduced aspirin action. We recently found that platelet MRP4 overexpression has a role in reducing aspirin action in patients after by‐pass surgery. Aspirin enhances MRP4‐mRNA levels in rat liver and drug administration transcriptionally regulates MRP4 gene expression through peroxisome proliferator‐activated receptor‐α (PPARα). Methods The effects induced by aspirin or PPARα agonist (WY14643) on MRP4 modulation were evaluated in vitro in a human megakaryoblastic DAMI cell line, in megakaryocytes (MKs) and in platelets obtained from human haematopoietic progenitor cell (HPC) cultures, and in vivo platelets obtained from aspirin treated healthy volunteers (HV). Results In DAMI cells, aspirin and WY14643 treatment induced a significant increase in MRP4 and PPARα expression. In human MKs grown in the presence of either aspirin or WY14643, MRP4 and PPARα‐mRNA were higher than in control cultures and derived platelets showed an enhancement in MRP4 protein expression. The ability of aspirin to modulate MRP4 expression in MKs and to transfer it to platelets was also confirmed in vivo. In fact, we found the highest MRP4 mRNA and protein expression in platelets obtained from HV after 15 days' aspirin treatment. Conclusions The present study provides evidence, for the first time, that aspirin treatment affects the platelet protein pattern through MK genomic modulation. This work represents an innovative and attractive approach, useful both to identify patients less sensitive to aspirin and to improve pharmacological treatment in cardiovascular high‐risk patients.